An Assessment of Movement and Dam Passage of Paddlefish in the Ohio River, West Virginia. - Welsh, Stuart; Zipfel, Katherine; Peters, Andrew; Hoffman, Cole; Layne, Cameron (Proceedings of the West Virginia Academy of Science, 2024)
Paddlefish (Polydon spathula), a large-bodied and highly migratory species of large river systems, has experienced population declines or extirpation in parts of its range. As an effort to reestablish Paddlefish populations in the Ohio River of West Virginia, the West Virginia Division of Natural Resources has periodically stocked Paddlefish, but post-stocking studies are needed to assess the status of the reintroduced population, including information on movements of Paddlefish or on their passage through navigation dams of the Ohio River. Using telemetry techniques, we monitored seasonal movements and assessed dam passage of five Paddlefish in the Robert C. Byrd pool of the Ohio and Kanawha rivers. Paddlefish were highly mobile with two individuals using the entire R.C. Byrd pool during the 11-month study period. The highest movement rates occurring during the expected spawning period of April and May, where all individuals frequented the upper section of the pool in Kanawha River. Downstream passage was documented for one individual at the R.C. Byrd lock during July 2023, but no evidence of passage was documented for the locks at Racine or Winfield. Tagging of additional Paddlefish is planned, which will increase sample size for future assessments and continue efforts toward the long-term conservation and management of Ohio River Paddlefish.